LEGAL JUSTICE IN PRESIDENTIAL IMPEACHMENT PRACTICE BETWEEN INDONESIA AND THE UNITED STATES OF AMERICA - Hanif Fudin (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
The constitution is approved as a law capable of guaranteeing human rights and protection of the constitution and past coordination, as well as being the corpus of the administration of the rule of law entity itself. Regarding the state of Indonesia and the United States, if examined by these two countries, they have similarities in the form of republican government or presidential system of government. However, on the contrary, in the impeachment transition, the two countries appear to be dichotomous both formally and materially. Therefore, this scientific article discusses reviewing the impeachment provisions of the Presidents of the two countries who agree to develop agreements and principles in checks and balances in trying to actualize the value of the country's legal justice. Therefore, in approving the discourse of research methods, descriptive-comparative methods are used with normative-philosophical and comparative-critical discussions. On that basis, this study discusses the practice of presidential impeachment in Indonesia to consider more legal justice, because it is through a legal process involving the Constitutional Court which implements practices in the United States that only involve the Senate and the House of Representatives which incidentally is a political institution. It considers the constitution in the basic law of the country.